2005
DOI: 10.2106/jbjs.d.02209
|View full text |Cite
|
Sign up to set email alerts
|

Results of Preoperative Pulmonary Function Testing of Adolescents with Idiopathic Scoliosis

Abstract: Some patients with adolescent idiopathic scoliosis may have clinically relevant pulmonary impairment that is out of proportion with the severity of the scoliosis, and this may alter the decision-making process regarding which fusion technique will produce an acceptable clinical result with the least additional effect on pulmonary function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
127
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(138 citation statements)
references
References 28 publications
9
127
1
1
Order By: Relevance
“…Some of these reports have concluded that the former is the main cause of the latter [8,9]. Other authors, by contrast, obtained similar results to those found in the present study and have been unable to establish a direct link between the severity of spinal deformity and lung function [35][36][37]. These discrepancies can be explained by the heterogeneity of the populations included in the different studies, where idiopathic scoliosis was frequently mixed with secondary scoliosis, and clinical subtypes, severity of chest deformities and smoking histories were very diverse.…”
Section: Lung Functionsupporting
(Expert classified)
See 1 more Smart Citation
“…Some of these reports have concluded that the former is the main cause of the latter [8,9]. Other authors, by contrast, obtained similar results to those found in the present study and have been unable to establish a direct link between the severity of spinal deformity and lung function [35][36][37]. These discrepancies can be explained by the heterogeneity of the populations included in the different studies, where idiopathic scoliosis was frequently mixed with secondary scoliosis, and clinical subtypes, severity of chest deformities and smoking histories were very diverse.…”
Section: Lung Functionsupporting
(Expert classified)
“…Many studies have already investigated lung function in patients with scoliosis, exploring, in particular, the relationships between the chest deformity and ventilatory impairment [5,8,9,[35][36][37]. Some of these reports have concluded that the former is the main cause of the latter [8,9].…”
Section: Lung Functionmentioning
confidence: 99%
“…Once documented, the progression of scoliosis needs to be addressed to arrest thoracic cage deformity and concomitant pulmonary compromise. (5) Thoracic cage deformity can arise intrinsically from fused ribs and/or secondarily from the curvature, rotation and shortening of the thoracic spine. Severe thoracic cage distortion leads to extrinsic restrictive lung disease from the diminution of lung volume under the convex rib hump and on the concave side, where the ribs impinge on the lung.…”
Section: Introductionmentioning
confidence: 99%
“…(7) Previous studies have indicated that severe scoliosis leads to poor pulmonary function. (2)(3)(4)(5)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) Since poor pulmonary function may lead to a higher incidence of postoperative pulmonary complications, preoperative pulmonary function tests (PFTs) have commonly been used to predict postoperative pulmonary complications. (14) However, there have been no detailed analyses of preoperative pulmonary function in relation to the Cobb angle, location of apical vertebrae and age in AIS.…”
Section: Introductionmentioning
confidence: 99%
“…Spinal surgeons are waiting for future studies on this promising new technique. Pulmonary function in patients with AIS related to surgical approaches Newton et al [22] evaluated preoperative pulmonary function data in 631 patients with AIS. In this group, the mean percentage of the predicted forced vital capacity fell below the American Thoracic Society threshold for normal pulmonary function (80 %) once the magnitude of the main thoracic curve exceeded 70°.…”
Section: Anterior Thoracoscopic Proceduresmentioning
confidence: 99%